The Use of Online Literature Circles to Enhance the Students’ Critical Reading Skills - Titi Rokhayati; Erna Alvionita (Journal of Languages and Language Teaching, 2022)
This research aims to find out whether using Online Literature Circles to enhance the student's critical reading skills is effective or not. This research belongs to quantitative research using a pre-experimental design. The population of this research is eleventh-grade students of SMK N 1 Puring in the academic year of 2020/2021 which consists of 382 students. The sample of this research is XI TKPI 1 consist of 34 students. The data were taken virtual from 17th May 2021 to 31st May 2021. The technique of the data collection is using a test. It was done by giving an online pre-test and online post-test. Meanwhile, the technique of data analysis used descriptive analysis and inferential analysis. The result of this research shows that the mean score of the pre-test is 49.79 which belongs to fairly sufficient category, and the mean score of the post-test is 70.79 which belongs to the good category. To see whether the hypothesis is accepted or rejected, the researchers use t-test through IBM SPSS 25. The result two-sided significant value is 0.000. Based on the 0.05 significant level, the computation shows the two-sided significance value is lower than 0.05 (0.000<0.05). Therefore, it can be concluded that Online Literature Circles is effective to enhance the students' critical reading skills at the eleventh-grade students of SMK N 1 Puring in the academic year of 2020/2021.